PENGEMBANGAN E-BOOK MATA PELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR DI SMP NEGERI 02 SUNGGUMINASA KABUPATEN GOWA. - Muh. Reski; Nurhikmah H; Farida Febriati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem found was the lack of learning media used by science teachers in the learning process. So the researchers developed this e-book with the aim of: 1) identifying the need for e-books, 2) developing e-book designs, 3) measuring the level of validity, practicality and effectiveness of e-books. This research uses an R&D approach and was developed using the ADDIE model. The research was carried out at SMP Negeri 02 Sungguminasa, Gowa Regency. with research subjects 25 students and science teachers. The research results show that the level of student needs is at 79% of required qualifications, teacher interviews are at 100%, qualifications are very much needed, material/content validation results are at 82.86% for good qualifications, media/design validation results are at 93.33% for qualifications. very good, the results of the student response assessment were in the percentage of 85% good qualifications and the teacher assessment response questionnaire was in the percentage of 80% good qualifications, and to measure effectiveness the one group pretest experimental method was used with an average score of 5.78 points and posttest with an average This value of 9.43 points indicates an increase in learning outcomes so that it is declared very effective. The conclusion of the research results is that the level of analysis of the need for E-books in science subjects is in the required qualifications and this E-book is very valid, practical and very effective. And can improve student learning outcomes.